1999
DOI: 10.1053/cp.1999.v66.a101210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of filgrastim treatment on inflammatory cytokines and lymphocyte functions*1

Abstract: Twenty-four healthy male volunteers received either placebo or 75, 150, or 300 microg filgrastim (recombinant methionyl human granulocyte colony-stimulating factor) for 12 days to study effects on monocytes and lymphocytes. In all filgrastim-treated groups, tumor necrosis factor alpha (TNF-alpha), interleukin-12 (IL-12), and interferon gamma (IFN-gamma) release by whole blood in response to endotoxin (lipopolysaccharide) was reduced. IL-12 added in vitro to lipopolysaccharide-stimulated blood of filgrastim-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 28 publications
0
42
1
Order By: Relevance
“…46,47 Th2 and DC2 polarization were found in healthy volunteers treated with filgrastim in vivo or in peripheral blood incubated with filgrastim in vitro, [48][49][50] supporting the expectation that the risk of chronic GVHD would be increased with the use of filgrastim-mobilized blood stem cells for allogeneic transplantation. We here describe a population of patients with chronic GVHD, the high-risk subgroup, some of whom had typical manifestations of both acute (eg, maculopapular rash and inflammatory diarrhea) and chronic (eg, lichenoid changes of the oral mucosa) GVHD.…”
Section: Discussionmentioning
confidence: 76%
“…46,47 Th2 and DC2 polarization were found in healthy volunteers treated with filgrastim in vivo or in peripheral blood incubated with filgrastim in vitro, [48][49][50] supporting the expectation that the risk of chronic GVHD would be increased with the use of filgrastim-mobilized blood stem cells for allogeneic transplantation. We here describe a population of patients with chronic GVHD, the high-risk subgroup, some of whom had typical manifestations of both acute (eg, maculopapular rash and inflammatory diarrhea) and chronic (eg, lichenoid changes of the oral mucosa) GVHD.…”
Section: Discussionmentioning
confidence: 76%
“…Although exogenous administration of G-CSF has not been associated with improved outcomes in patients with pneumonia and/or severe sepsis in large clinical trials (310,311,361), melioidosis may differ from infections due to other organisms because of the key role of neutrophils in patients with recognized risk factors for neutrophil defects. G-CSF may reverse these defects (312), act to counter inflammatory cytokines (187,471), and increase intracellular concentrations of antibiotics (131,248,298). The use of G-CSF in patients with septic shock due to melioidosis was associated with a large fall in mortality (from 95 to 10%); however, several confounding factors may at least partly account for this effect (84).…”
Section: Management Of Sepsis Syndromementioning
confidence: 99%
“…G-CSF has been shown to inhibit the secretion of Th1 cytokines by T cells, thus polarizing them toward a Th2 cytokine (IL-4 and IL-10) phenotype (9,12,13,15,59). We (our unpublished results) and others have also demonstrated that G-CSF suppresses responsiveness of conventional T cells, resulting in impairments in the ability of T cells to proliferate, and to differentiate in response to IL-2, mitogens (PHA and Con A), and allo-Ags (14, 16, 18, 20, 59 -62).…”
Section: Discussionmentioning
confidence: 99%